Development of Powtoon-Based Animated Video Learning Media on Atmospheric Layers for Grade X Students at SMAN 1 Air Putih in the 2024/2025 Academic Year - Mery Christin Adventina Sitinjak; Restu Restu (JURNAL PENDIDIKAN, 2025)
The low level of student understanding of the atmospheric layer material and the limited use of interactive digital learning media are major obstacles in the geography learning process at SMA Negeri 1 Air Putih. Teaching is still dominated by conventional methods such as whiteboards and textbooks, making it difficult for students to grasp abstract concepts. This research aims to develop an engaging and interactive animated video learning media using the Powtoon application. This research employed the Research and Development (R&D) method with the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 28 students of class X-3. Data were collected through observation, interviews, questionnaires, and tests. Validation was conducted by a subject matter expert, a media expert, and a geography teacher. The results showed that the developed media received a feasibility score of 90% from both the content and media experts, categorized as “Highly Feasible.” Practicality testing by the teacher yielded a score of 95%, indicating the media is “Highly Practical.” Effectiveness testing through pretest and posttest analysis using the N-Gain formula resulted in a score of 0.77 or 76.81%, categorized as “Effective.” Thus, the Powtoon-based animated video media is proven to be feasible, practical, and effective, and can serve as an innovative alternative to improve student learning outcomes in geography, particularly in learning the atmospheric layer material.